2014
DOI: 10.1371/journal.pone.0082880
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Gliclazide as Treatment for Type 2 Diabetes: A Systematic Review and Meta-Analysis of Randomized Trials

Abstract: Objective and DesignGliclazide has been associated with a low risk of hypoglycemic episodes and beneficial long-term cardiovascular safety in observational cohorts. The aim of this study was to assess in a systematic review and meta-analysis of randomized controlled trials the safety and efficacy of gliclazide compared to other oral glucose-lowering agents (PROSPERO2013:CRD42013004156)Data SourcesMedline, EMBASE, Clinicaltrials.gov, Trialregister.nl, Clinicaltrialsregister.eu and the Cochrane database.Selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 36 publications
(142 reference statements)
0
48
0
4
Order By: Relevance
“…25,26 A meta-analysis of SU trials concluded that severe hypoglycaemia was rare with gliclazide, especially if the dose does not exceed 240 mg daily. Non-severe hypoglycaemia was seen mainly in those on 320 mg daily.…”
Section: Sulfonylureasmentioning
confidence: 99%
“…25,26 A meta-analysis of SU trials concluded that severe hypoglycaemia was rare with gliclazide, especially if the dose does not exceed 240 mg daily. Non-severe hypoglycaemia was seen mainly in those on 320 mg daily.…”
Section: Sulfonylureasmentioning
confidence: 99%
“…Reduced TNF-α and elevated adiponectin levels correlate with improved insulin resistance, which is thought to be associated with low blood PAI-1 levels [34,35]. Furthermore, glibenclamide and glimepiride carry a higher risk of hypoglycemia thangliclazide [36]. Low blood glucose levels increase blood PAI-1 levels [37], which may beanother reason why blood PAI-1 levels are lower after using gliclazide than after using glimepiride.…”
Section: Discussionmentioning
confidence: 99%
“…One of the other main advantages of gliclazide is its safety in severe renal failure [5]. In addition, two metaanalyses have reported that of all the sulfonylureas, gliclazide is associated with the lowest risk of hypoglycaemia [6]. For example, the hypoglycaemic event rate for gliclazide is 50% lower than that for glimepiride [7] and is comparable to that for dipeptidyl peptidase-4 inhibitors [8,9].…”
mentioning
confidence: 99%